Implementasi Smart City Berbasis Teknologi Berkelanjutan di DKI Jakarta: Analisis Smart Environment, Smart Economy, dan Smart People - Sari Setyo Ningrum; Maria Kristina Lusia Geong; Sekar Rini Pratiwi; Aira Fairana; Elpi Nainggolan; Ida Kusnawati Tjahjani (Lambung Mangkurat University Press, 2026)
This study aims to analyze the implementation of a Smart City based on sustainable technology in the province of DKI Jakarta, focusing on three main pillars: Smart Environment, Smart Economy, and Smart People. The study employs a descriptive qualitative approach. The results show that the implementation of the Smart Environment pillar is realized through innovations such as the Internet of Things (IoT)-based environmental quality monitoring system, the Flood Monitoring Dashboard, and the Jakarta Environmental Monitoring System (JEMS). In the Smart Economy pillar, the transformation toward a digital economy and a less-cash society has encouraged inclusive economic growth through programs such as Future City Hub and Open Data Jakarta. Meanwhile, the Smart People pillar emphasizes improving digital literacy and public participation through programs such as JSC Goes to School and Kelas Warga. The main supporting factors for Smart City implementation include consistent government regulations and strong digital infrastructure. However, challenges such as unequal digital literacy and uneven public participation remain as obstacles. Overall, this study emphasizes that the success of Smart City implementation in Jakarta depends on the synergy between the government, society, and technology that is oriented toward sustainability. Keywords: Smart City, Sustainable Technology, Smart Environment, Smart Economy, Smart People